The Effectivity of Chitosan Usage on The Improvements of Epithelialization in Diabetic Wounds Regio Anterior Cruris Dorsalis Pedis Sinistra A Case Report - Uyunul Jannah; Moh Gifari S; Takdir Tahir; Saldy Yusuf (Jurnal Keperawatan Respati Yogyakarta, 2020)
Treatments of diabetic ulcer are very essential to prevent further ulceration damage. Insufficient treatment of the wound can consequence in an infection that will have an impact upon the amputation. One of the antimicrobial wound dressing in the treatment of ulcus diabetic is chitosan. Therefore, this report aims to assess the effectivity of the usage of chitosan gel as a primary dressing for epithelial progression in diabetic ulcer at the wound care clinic of ETN Center, Makassar. Methods, this study was conducted on one patient, a female, 38 years old with random blood glucose 239 mg/dl. The wound occurred in April 2019, the wound has been experienced about three months and then followed prospectively starting 8th July until 1st August 2019 with 8 treatments. Treating the wound uses chitosan gel as a primary dressing and looks at the development process of the wound, especially the progress of the epithelium using the modified Bates-Jansen Wound Assessment Tool. Results, the comparison of treatment results using chitosan in the first and eighth treatments (25 days) respectively slough 10% and 5%, granulation 75% and 60%, and epithelialization 15% and 35%. While the size of the wound 41 x 17 cm to 32 x 13 cm. Conclusion, chitosan gel as a primary dressing plays an important role in helping the wound healing process as indicated by an increase in epithelium and reduction in wound size.